Tumour Necrosis Factor-α Production and Immune Cell Activation in Tuberculous Meningitis - C. M. Mastroianni; F. Paoletti; C. Valenti; A. P. Massetti; V. Vullo; S. Delia (Mediators of Inflammation)
The local production of tumour necrosis factor-α (TNFα) was evaluated in the cerebrospinal fluid (CSF) from ten patients with tuberculous meningitis (TBM). The degree of intrathecal immune activation was also studied by assessing the CSF levels of β2-microglobulin (β2-M) and adenosine deaminase activity (ADA). Results indicate that elevated CSF concentrations of TNFα, β2-M and ADA were found in all TBM patients. Moreover, TNFα is produced and selectively concentrated for a long period of time, while β2-M and ADA values progressively decline during the course of TBM. Our findings suggest that in TBM patients, after an early activation of immune cells, there is an enhanced and continuous production of TNFα at the site of infection.